ANALISIS PENYERAPAN TENAGA KERJA PADA INDUSTRI MANUFAKTUR BESAR DAN SEDANG PADA TINGKAT KABUPATEN/KOTA DI PROVINSI JAWA TIMUR (2017-2019) - Novi Rosyana; Aris Soelistyo (Program Studi Ekonomi Pembangunan, 2020)
The study is intended to determine the analysis of the absorption of workers working in the industry of manufacturing large and medium at the level of districts / cities diprovinsi Java East in 2017-2019 . Expansion absorption of energy work is very necessary to keep pace with the rate of growth of the population , with the construction sector of the industry especially industrial manufacturing is expected to absorb over many workers work . The variable that is used is the number of industries , the value of production , and wage minimum using analysis regression multiple is regression panel data with 38 sample districts / cities in the province of Java east , the results of the study showed that the results of a number of industries , the value of production has a relationship that is positive and signinifikan , and wage minimum impact negatively not significant .